1980
DOI: 10.1093/nar/8.15.3393
|View full text |Cite
|
Sign up to set email alerts
|

The extraction by micrococcal nuclease of ghucocorticoid receptors and mouse mammary tumor virus DNA sequences is dissociated

Abstract: Glucocorticoid receptors (RG) and mammary tumor virus (MM-TV) DNA sequences were extracted by micrococcal nuclease digestion from the nuclei of C3H mouse mammary tumor cells in order to specify their relative distribution in chromatin. RG was labelled and translocated into the nuclei by incubating cells with 3H Dexamethasone (3H Dex). The purified nuclei were then treated at 2 degrees C with micrococcal nuclease. Three chromatin fractions were successively obtained: an isotonic extract (ne3H1), ahypotonic extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1982
1982
1984
1984

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…This points to the importance, for hormone action, of the site of retrovirus integration and, presumably, of chromatin conformation. This is consistent with the observation (Andre et al, 1980) that in the normal host (mouse mammary tumour) cell, mild nuclease treatment of the nuclei preferentially releases the receptor together with a small proportion of MTV DNA. This fraction, containing the few glucocorticoidsensitive copies of MTV DNA, would correspond to 'active chromatin'.…”
Section: Involvement Of Chromatinsupporting
confidence: 92%
“…This points to the importance, for hormone action, of the site of retrovirus integration and, presumably, of chromatin conformation. This is consistent with the observation (Andre et al, 1980) that in the normal host (mouse mammary tumour) cell, mild nuclease treatment of the nuclei preferentially releases the receptor together with a small proportion of MTV DNA. This fraction, containing the few glucocorticoidsensitive copies of MTV DNA, would correspond to 'active chromatin'.…”
Section: Involvement Of Chromatinsupporting
confidence: 92%
“…As one approach to demonstrating possible heterogeneity of nuclear receptors, several investigators are studying the distribution of receptors in different fractions of chromatin. Thus, fractionation of chromatin or nuclei by ion-exchange chromatography or nuclease digestion has suggested that the nuclear receptors for steroid and thyroid hormones are nonrandomly distributed on the chromatin (Charles et at., 197 5;de Boer et at., 1978;Franceschi and Kim, 1979;Andre et at., 1980;Cidlowski and Munck, 1980;Davies et at., 1980;Jump and Oppenheimer, 1980;Scott and Frankel, 1980;Pavlik and Katzenellenbogen, 1982). Other investigators have observed that components with the characteristics of steroid hormone receptors are also localized in non chromatin fractions derived from their target cell nuclei.…”
Section: The Nature Of Receptorsmentioning
confidence: 99%
“…Thus, it was reported that estrogen treatment (and, therefore, the presence of hormone-receptor complexes in nuclei) enhances the overall sensitivity to DNase I of the genome (Senior and Frankel, 1978) as well as specifically of that of the ovalbumin gene (Garel and Axel, 1976;Weintraub and Groudine, 1976;. Micrococcal nuclease has also been reported to preferentially release from chromatin the nuclear receptor for estrogen (Andre et at., 1978(Andre et at., , 1980 and thyroid hormone (Gardner, 1978). Again, of course, the starting materials are complex and poorly characterized, and the results therefore difficult to interpret.…”
Section: The Rote Of Nuclear Receptors In Transcriptionmentioning
confidence: 99%
“…It is likely that one of the principal effects of steroids in the nucleus is an alteration in the transcriptional rates of specific genes. Although numerous studies have been undertaken to characterize the in vivo binding of steroid hormone-receptor complexes to chromatin (10)(11)(12)(13)(14) and other nuclear components (15,16), the crucial nuclear acceptor molecules for the steroidreceptor complex have not yet been identified.…”
mentioning
confidence: 99%